Strengthening Character Education through Participatory Scout Extracurricular Mentoring in an Indonesian Madrasah - M Riyan Hidayat; Diyana (CV. Jalan Cendikia, 2026)
Strengthening students’ character education requires learning spaces that go beyond formal classroom instruction. This community service program aimed to strengthen students’ character through structured Scout extracurricular mentoring at MTs Daarun Najaa Sumber Hidup, Ogan Komering Ilir. The program employed a participatory service-learning intervention involving the madrasah, Scout coaches, teachers, Mandiri KKN students, and student participants. The activities were implemented through four stages: needs assessment, program design, implementation, and evaluation-reflection. Data were collected through participatory observation, field notes, documentation, informal interviews, and student feedback, then analyzed descriptively and thematically. The results show that Scout mentoring helped transform routine extracurricular activities into value-oriented character education practices. The program produced a character-based mentoring design and strengthened students’ religiosity, discipline, responsibility, cooperation, leadership, and social concern through opening assemblies, marching practice, squad work, environmental care activities, leadership rotation, and value reflection. Students became more orderly, more responsible in completing squad tasks, more willing to cooperate, and more confident in taking leadership roles. This program implies that Scout extracurricular activities can serve as a practical character education strategy when supported by clear behavioral indicators, consistent mentoring, reflective activities, and active involvement of Scout coaches and teachers.